PHARMACO-TOXICOLOGICAL RESEARCH AND ESTABLISHMENT OF QUALITY STANDARDS FOR CAPSULES BASED ON THE ARTICHOKE OF KEY BARBARED IN UZBEKISTAN - Mirrakhimova, Tanzila A. (International Journal of Psychosocial Rehabilitation, 2020)
This work presents the results of pharmaco-toxicological studies and established quality standards for the preparation of 450 mg based on prickly artichoke. Pharmacological studies on the study of acute toxicity showed that the “LD50” of the studied preparation of 450 mg capsules on the basis of prickly artichoke was> 12500 mg / kg. The studied capsules at a dose of 1000 mg/kg had an equivalent choleretic effect with the drug comparison tablets “Chophytol” manufactured by Laboratories Roza-Phytopharma, France. A 3% aqueous solution of 450 mg capsules at a dose of 300 mg/kg enhanced the bile excretory function of rat liver during intoxication with carbon tetrachloride and had an equivalent hepatoprotective effect with the reference drug. Embryotoxic and teratogenic effects of the drug in doses of 300 mg/kg and 1500 mg/kg with the introduction of "per os" were not detected. Established quality standards for 450 mg capsules based on prickly artichoke. The drug is standardized in accordance with the requirements of regulatory documentation for the following indicators: description, authenticity, average weight, disintegration, heavy metals, microbiological purity, quantitative determination.